Drop Size Distribution in Agitated Contactor: A Review - Hamed, Marwa S.; Hasan, Basim O.; Znad, Hussein T.; Al-Zuraiji, Sahir M. (Al-Nahrain Journal for Engineering Sciences, 2024)
The breakage rate of liquid drops in the dispersed phase is a key way to improve the heat and mass transfer between the continuous/dispersed phases. This work includes a review of experimental results of liquid drop breakage in an agitated tank. The study highlighted the experimental conditions that were investigated as well as the important findings about the impact of operating conditions on some breakup parameters. The conflicts and discrepancies in the findings of those studies were identified and analyzed. The review found that many experimental parameters affect the drop breakage rate. The breakage probability (BP), number of fragments, and breakage time (BT) are direct functions of power input.